Therapeutic Effect of Autologous Serum Eye Drops on Aqueous Tear-Deficiency and Evaporative Tear-Deficiency Cases - Kukuh Prasetyo; Susi Heryati (The Indonesian Ophthalmologists Association (IOA, Perhimpunan Dokter Spesialis Mata Indonesia (Perdami)), 2016)
Background: To evaluate therapeutic effect of autologous serum eye drops on aqueous tear-deficiency(ATD) and evaporative tear-deficiency (ETD) cases. Case Illustration: Two cases were taken from Infection and Immunology Unit of Cicendo NationalEye Center. First case was 21 year-old male with a complaint of red, itchy, and foreign-body sensationon both eyes, low result in Schirmer test and tear-break up time then diagnosed with dry eyes withsuspicion of type I Sjogren syndrome (ATD case). Second case was 24 year-old female with a complaintof red and watery eyes, normal result of Schirmer test and low tear-break up time, then diagnosed withacute blepharitis (ETD case). Both were given autologous serum eye drops for 4 weeks and underwentexamination for 3 times. Variables examined were: subjective symptoms using OSDI score, tear-breakup time, Schirmer test (both Schirmer test I with and without anesthetic agent; and Schirmer test II),and ocular surface evaluation using NEI staining score. Conclusion: Autologous serum eye drops has therapeutic effect on both cases of aqueous tear-deficiencyand evaporative tear-deficiency. Further experiment with more samples and longer examination periodis needed to compare which best treated using autologous serum eye drops.Â Keywords: autologous serum eye drops, aqueous tear-deficiency, evaporative tear-deficiency, dry eye